Moonlighting Biochemistry of Cysteine Synthase: A Species-specific Global Regulator. Issue 22 (5th November 2021) - Singh, Ravi Pratap; Saini, Neha; Sharma, Gaurav; Rahisuddin, R.; Patel, Madhuri; Kaushik, Abhishek; Kumaran, S.
Graphical abstract: Highlights: Moonlighting proteins are a subclass of extreme multifunctional proteins (EMPs) whose functions are unrelated. Mapping the extreme multifunctional space (EMS) of a protein is the first step in mapping the moonlighting space of an EMP. We developed an integrated prediction and validation framework for expanding the EMS of Cysteine Synthase (CS). CS interacts with proteins involved in diverse metabolic activities in a species-specific manner. High resolution experimental methods provide insights into biochemistry of EMS and moonlighting features. Abstract: Cysteine Synthase (CS), the enzyme that synthesizes cysteine, performs non-canonical regulatory roles by binding and modulating functions of disparate proteins. Beyond its role in catalysis and regulation in the cysteine biosynthesis pathway, it exerts its moonlighting effect by binding to few other proteins which possess a C-terminal "CS-binding motif", ending with a terminal ILE. Therefore, we hypothesized that CS might regulate many other disparate proteins with the "CS-binding motif". In this study, we developed an iterative sequence matching method for mapping moonlighting biochemistry of CS and validated our prediction by analytical and structural approaches. Using a minimal protein-peptide interaction system, we show that five previously unknown CS-binder proteins that participate in diverse metabolic processes interact with CS in a species-specific manner. Furthermore, results show that signatures of protein–protein interactions, including thermodynamic, competitive-inhibition, and structural features, highly match the known CS-Binder, serine acetyltransferase (SAT). Together, the results presented in this study allow us to map the extreme multifunctional space (EMS) of CS and reveal the biochemistry of moonlighting space, a subset of EMS. We believe that the integrated computational and experimental workflow developed here could be further modified and extended to study protein-specific moonlighting properties of multifunctional proteins.